2019
DOI: 10.1155/2019/6750864
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Bloodstream Infections and Antimicrobial Susceptibility Patterns: A Nine-Year Retrospective Study at St. Dominic Hospital, Akwatia, Ghana

Abstract: Background. Bloodstream infections are among the top causes of morbidity and mortality in people of all ages, especially in immunocompromised patients in sub-Saharan Africa. This study aimed at describing the epidemiology of bloodstream infections and antimicrobial susceptibility pattern over a nine-year period at St. Dominic Hospital, Akwatia, in the Eastern Region of Ghana. Method. This study retrospectively analysed data from 4,489 patients who were referred to the Laboratory Department for blood culture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
4
18
0
1
Order By: Relevance
“…The isolation rate of blood culture positive cases in our study was 28.09%. This was similar to previous reports from India and Ethiopia [2,13,14] but however showed variation with other studies [1,12,[15][16][17][18], as shown in Table 5. Variations in blood culture positive rates may be due to the use of different laboratory diagnostic procedures, different patient populations, underlying disease conditions, hospital types, geographical locations and differences in the infection control policies [10,13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The isolation rate of blood culture positive cases in our study was 28.09%. This was similar to previous reports from India and Ethiopia [2,13,14] but however showed variation with other studies [1,12,[15][16][17][18], as shown in Table 5. Variations in blood culture positive rates may be due to the use of different laboratory diagnostic procedures, different patient populations, underlying disease conditions, hospital types, geographical locations and differences in the infection control policies [10,13].…”
Section: Discussionsupporting
confidence: 91%
“…Blood stream infections (BSIs) are the leading cause of morbidity and mortality in Sub-Saharan Africa especially in immune-compromised patients, yet few facilities have been able to maintain surveillance [1,2]. Globally, Blood stream infection affects about 30 million people and accounts for 6 million deaths, with 3 million new born and 1.2 million children suffering from sepsis annually [1]. Advances in medicine, increasing use of invasive devices, prolonged hospital stay, immunosuppressive therapy, neutropenia, and organ transplantation are some of the risk factors associated with blood stream infections [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Blood infections are a substantial reason for morbidity and mortality of patients, particularly in developing countries. 2 If left untreated, bloodstream infections may lead to more dangerous infections, involving all organs and ultimately death. 3 Among the various types of nosocomial infections, bloodstream infections are a very serious health problem in hospital wards globally.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus'ta metisilin direnci, mikrodilüsyon yöntemi kullanılarak oksasilin ve sefoksitin testiyle doğrulandı. Enterobacteriaceae için karbapenem direnci CLSI kriterlerine göre meropenem ve imipenem minimum inhibitör konsantrasyonu (MIC) >2 mg/ml ve sefmetazol MIC >64 mg/ml olması olarak kabul edildi (7,12,13).…”
Section: Yöntemlerunclassified